Age-related changes in adrenergic alpha 1, alpha 2, and beta receptors of rat white fat cell membranes: an analysis using [3H]bunazosin as a novel ligand for the alpha 1 adrenoceptor. - T Kobatake; Y Watanabe; Y Matsuzawa; K Tokunaga; S Fujioka; T Kawamoto; Y Keno; S Tarui; H Yoshida (Journal of Lipid Research, 1991)
Age-related changes in alpha 1-, alpha 2-, and beta-catecholamine receptors on membrane of rat epididymal fat cells were investigated. Both young (6 weeks old, weight about 190 g) and aged (20 weeks old, weight about 490 g) Sprague-Dawley male rats were used. For the alpha 1-adrenoceptor binding experiment, we developed a novel analytical method using the hydrophilic alpha 1-receptor selective antagonist, [3H]bunazosin. The binding of [3H]bunazosin to its binding sites was rapid, reversible, saturable, and stereospecific. Scatchard binding analysis showed a single class of binding site. The sites were characterized as alpha 1-adrenoceptors by inhibition experiments using various agonists and antagonists. The number of maximum binding sites (Bmax) of alpha 1-receptor binding was 37.0 +/- 6.5 (young) versus 24.0 +/- 3.2 (aged) fmol/mg protein (P less than 0.01). [3H]Rauwolscine and [3H]CGP-12177 were used for alpha 2- and beta-receptor binding, respectively. In alpha 2-receptor detection using [3H]rauwolscine as a ligand, Bmax increased markedly from 19.8 +/- 4.9 to 86.2 +/- 19.5 fmol/mg protein (P less than 0.01). In contrast, Bmax for beta-receptor decreased from 69.7 +/- 9.7 to 45.4 +/- 13.9 fmol/mg protein with increasing rat age (P less than 0.05). Kd showed no change in each of the binding experiments between young and aged rats. The cell volume increased from 0.07 +/- 0.02 to 0.15 +/- 0.06 nl. It is implied that anti-lipolytic activity strengthened on the whole mainly with the marked increase of alpha 2-receptor number and decrease of beta-receptor number.(ABSTRACT TRUNCATED AT 250 WORDS)